Identification of the oxidation stress-related gene signatures and functional verification of MINK1 in prostate cancer cells - Shuai Liang; Shuhua Zhou; Yangshuo Tang; Moyan Xiao; Ke Ye (PLoS ONE, 2026)
Background A major challenge facing prostate cancer (PCa) cells is oxidative stress, yet the precise role and underlying mechanisms remain inadequately elucidated. The study sought to investigate the association between oxidative stress and PCa prognosis, as well as to identify potential regulatory pathways involved. Methods Oxidative stress-related genes and data were sourced from the Genecards, TCGA-PRAD, and GSE16560 databases. A risk model was developed using machine learning, including random forest and LASSO analyses. Survival analysis, functional and immune infiltrate analysis, as well as immunotherapy analysis were performed. The expression of MINK1 was examined, and the effects of MINK1 silencing on cell biological activities (including proliferation, migration, and invasion) were investigated, alongside analyses of MINK1-related pathways. Results Four genes (BCO1, MINK1, TAF1C, and MIS18BP1) were identified and utilized to develop an oxidative stress-risk score (OS-score). The high-OS-score predicted a poor prognosis, and OS-score was an independent prognostic factor for PCa. The OS-score demonstrated a positive correlation with CD8 + T cells, activated CD4 + T cells, and macrophages. Patients classified within the high-OS-score group were more effective in anti-PD-1 therapy (Nominal P = 0.001, Bonferroni corrected P = 0.011). A significant disparity was observed in the efficacy of immune checkpoint inhibitor treatment between the high- and low-OS-score groups ( P = 1.1 × 10 −9 ), with a higher proportion of responders in the high-OS-score group compared to non-responders. The key oxidative stress gene, MINK1, was experimentally validated and found to be highly expressed in PC-3 and DU145 cell lines. Silencing MINK1 resulted in decreased proliferation, migration, and invasion activity. Additionally, MINK1 knockdown induced G0/G1 phase arrest and inhibited nuclear translocation of NF-κB. Conclusion In summary, oxidative stress is associated with a poor prognosis in PCa. Oxidative stress-related gene MINK1 may regulate the cell biological activity through cell cycle and NF-κB signaling pathway. This study may provide new clues for the identification and development of new markers for the diagnosis and prognosis of PCa patients.